Effect of citric acid and heat treatment on the content of less-polar ginsenosides in flower buds of Panax ginseng. Issue 2 (1st February 2022) - Gao, Dan; Kim, Jin Hyeok; Vinh, Le Ba; Seo, Eun-Young; Yang, Seo Young; Cho, Chong Woon; Kim, Young Ho; Kim, Kyung Tae; Sim, Jaehoon; Kang, Jong Seong
Abstract: Ginseng flower bud (GFB), as an inexpensive part of Panax ginseng, attracted significant attention as a beneficial functional food with medicinal potentials due to its high content of ginsenosides. A few studies focused on the utilization of heat treatment and citric acid treatment to process ginseng flowers, converting its polar ginsenosides into rare ginsenosides to improve its biological activities. Thus, in this study, we compared the changes of ginsenosides in GFB after citric acid and heat treatment by HPLC method. The results revealed that less-polar ginsenoside, Rg6 and F4, increased to 1.01 and 0.27% by heat treatment, respectively. Further, ginsenoside F2 increased to 1.13% with 1 M citric acid treatment. Furthermore, based on the combination of these two processing methods for the first time, the conversion rate of less-polar ginsenosides surged to 80%. The content of ginsenoside Rg3(s) and Rg5 increased to 1.509 and 1.871%, respectively, by simultaneous heat and citric acid treatment. Therefore, a processing approach that simultaneously performs heat and citric acid treatments has been proposed, and this considerably inexpensive and convenient processing method could be applied to the processing of GFBs and produce less-polar ginsenosides.